Penyuluhan Fisioterapi pada Komunitas Anak & Remaja tentang Skoliosis di Sekolah Dasar Anak Saleh Malang, Mojolangu, Kota Malang - Wanda Alifia Chaerani; Sri Sunaringsih Ika Wardojo; Eleonora Elsa Sucahyo (Rena Cipta Mandiri, 2025)
Scoliosis is a spinal abnormality with lateral deviation that often appears during the growth period of children and adolescents, especially school-age children. This condition can cause postural disorders, back pain, and activity limitations if not addressed early. Physiotherapy counseling plays a crucial role in raising awareness among schoolchildren and teachers regarding the early detection and prevention of scoliosis. The counseling activity was conducted at Anak Saleh Elementary School in Malang with 37 sixth-grade students (16 boys, 21 girls). The implementation method included interactive education, demonstrations of simple posture checks, and back muscle stretching exercises. Evaluation results showed an increase in students' understanding of the signs of scoliosis, the importance of correct sitting posture, and scoliosis prevention exercises. This activity has implications for increasing elementary school children's knowledge about musculoskeletal health, particularly posture, and is expected to encourage a healthy lifestyle from an early age.